Deskripsi Pembelajaran Diferensiasi Berbantuan Media Digital pada Materi Pernapasan di SMPN 13 Sungai Kakap - Salim (Jurnal Pendidikan Edukasi Kusuma Bangsa, 2024)
Differentiated learning is a teaching and learning process where students can learn subject matter according to their abilities, likes and needs so that they do not get frustrated and feel like they have failed in their learning experience. This kind of learning has not been carried out by many teachers. Due to limited information obtained. So by making this written work, it can increase the teacher's information in carrying it out. Type of qualitative research. Data collection techniques are tests, observation and documentation. The number of research samples was 21 students in class 8A of Junior High School 13 Sungai Kakap. Based on the learning implementation scenario, differentiated learning has been proven. This can be seen from the start of learning preparation which groups or maps learning needs based on students' learning styles. Here there are 3 student learning styles including auditory, audio-visual and kinesthetic. The conclusions of this research include that the learning scenarios in differentiated learning designs have been proven to be real because of the content differentiation, process differentiation and product differentiation in the design. Learning outcomes of differentiated learning assisted by digital media on human respiratory system material in class 8 at Junior High School 13 Sungai Kakap with a knowledge score of 79.52 (good), a skills score of 90 (very good), and an attitude score of very good.